A Niche-Like Culture System Allowing the Maintenance of Primary Human Acute Myeloid Leukemia-Initiating Cells: A New Tool to Decipher Their Chemoresistance and Self-Renewal Mechanisms. (3rd February 2014) - Griessinger, Emmanuel; Anjos-Afonso, Fernando; Pizzitola, Irene; Rouault-Pierre, Kevin; Vargaftig, Jacques; Taussig, David; Gribben, John; Lassailly, François; Bonnet, Dominique
Abstract : This paper presents a culture system that can be used as an in vitro surrogate for xenotransplantation and that has the potential to dramatically increase the throughput of the investigation of leukemia-initiating cells, providing the means to identify and target the functionality of the different signaling pathways involved in the maintenance and resistance of leukemia-initiating cells to improve acute myeloid leukemia treatments. Abstract: Acute myeloid leukemia-initiating cells (LICs) are responsible for the emergence of leukemia and relapse after chemotherapy. Despite their identification more than 15 years ago, our understanding of the mechanisms responsible for their self-renewal activity and their chemoresistance remains poor. The slow progress in this area is partly due to the difficulty of studying these cells ex vivo. Indeed, current studies are reliant on xenotransplantation assays in immunodeficient mice. In this paper, we report that by modeling key elements of the bone marrow niche using different stromal feeder layers and hypoxic culture conditions, we can maintain LICs over at least 3 weeks and support their self-renewal properties demonstrated through primary and secondary successful xenograft. We provide a proof of principle that this niche-like culture system can be used to study LIC chemoresistance following in vitro cytarabine treatment similarly to the xenograft chemotherapy model. We found that although LICs are believed to be more chemoresistant than non-LICs, functionally defined LICs are not enriched after cytarabine treatment, and heterogeneity in their resistance to treatment can be seen between patients and even within the same patient. We present a culture system that can be used as an in vitro surrogate for xenotransplantation and that has the potential to dramatically increase the throughput of the investigation of LICs. This would further provide the means by which to identify and target the functionality of the different signaling pathways involved in the maintenance and resistance of LICs to improve acute myeloid leukemia treatments.